Contribuições para o fracasso ou sucesso? o papel da escola pública no processo de interrupção ou continuidade da formação escolar de jovens de origem popular - Gomes, Nathalia Gonçalves (2009)
This research is to investigate whether the school is encouraging the public school students to pursue higher levels of education after completing this stage of schooling. This question was raised by the data revealed by the Universidade Federal Fluminense s vestibular 2005, which on its percentage of subscribers, had a very small number of students from public primary education compared to the percentage of students from the private institutes (for becomes more unequal when put in comparison the percentage of students passed the selection process). Given this situation, was proposed an empirical investigation in a school in the state system of education, located in the oceanic region of Niterói, in order to identify the school's actions - in his set of actors - to make the transition of these students for higher studies, particularly for public institutions. In addition to the school's actions are often aimed at identifying the reasons given by the students to justify the situation of resignation to the waves of public universities. The survey consisted of three steps: a) literature review; b) questionnaires and; c) interviews. In the first phase, we surveyed relevant products in the field of Sociology of Education, in the field of educational inequalities. At that stage it was decided to elect two benchmarks that guided the next steps of research, both from the French School: Pierre Bourdieu and Bernard Lahire. In the second stage, questionnaires were filled with students and teachers. These questionnaires were intended to create frames of reference on the perceptions of students and teachers on the problems outlined here. Quantitative research has proposed percentage reductions on elements related to the phenomenon studied, but by their nature, had been unable to explain the conditions under which these results validate themselves. In the third stage of research, interviews were conducted with samples of the population studied in the previous step and with members of the teaching staff of the school. This phase was especially important for understanding the many variables that require the construction of the scenarios outlined by the quantitative phase. The study reveals that, among other reasons, the failure of public school students on the vestibular public institutions of higher education is by lack of motivation from the students themselves, caused by the poor quality of education offered in schools of basic education and lack information about these selection processes in these establishments.